Optimising the scan delay for arterial phase imaging of the liver using the bolus tracking technique. - Chan, R.; Kumar, G.; Abdullah, B.; Ng, K.H.; Vijayananthan, A.; Mohd Nor, H.; Liew, Y. (2011)
OBJECTIVE: To optimize the delay time before the initiation of arterial phase scan in the detection of focal liver lesions in contrast enhanced 5 phase liver CT using the bolus tracking technique. PATIENTS AND METHODS: Delay - the interval between threshold enhancement of 100 hounsfield unit (HU) in the abdominal aorta and commencement of the first arterial phase scan. Using a 16 slice CT scanner, a plain CT of the liver was done followed by an intravenous bolus of 120 ml nonionic iodinated contrast media (370 mg I/ml) at the rate of 4 mL/s. The second phase scan started immediately after the first phase scan. The portal venous and delay phases were obtained at a fixed delay of 60 s and 90 s from the beginning of contrast injection. Contrast enhancement index (CEI) and subjective visual conspicuity scores for each lesion were compared among the three groups. RESULTS: 84 lesions (11 hepatocellular carcinomas, 17 hemangiomas, 39 other hypervascular lesions and 45 cysts) were evaluated. CEI for hepatocellular carcinomas appears to be higher during the first arterial phase in the 6 seconds delay group. No significant difference in CEI and mean conspicuity scores among the three groups for hemangioma, other hypervascular lesions and cysts. CONCLUSION: The conspicuity of hepatocellular carcinomas appeared better during the early arterial phase using a bolus tracking technique with a scan delay of 6 seconds from the 100 HU threshold in the abdominal aorta.